Modification of einkorn flours via lactic acid fermentation: changes in techno-functional and rheological properties - Kiymaz, Burcu Mine; Ozturk, Eylul; Ozcan, Yilmaz; Toker, Omer Said; Arici, Muhammet (SPRINGER, 2026)
Fermentation has emerged as a promising bioprocessing strategy to enhance the nutritional and functional qualities of cereal grains naturally. In this study, the powder properties, functional, and rheological properties of mature and immature einkorn wheat flours were evaluated for five days, based on the effects of lactic acid fermentation using Lactiplantibacillus plantarum. Viable cell count increased rapidly within the first 24 h of fermentation, accompanied by a sharp decrease in pH. Bulk and tapped densities decreased during fermentation, while Carr's index and Hausner ratio indicated a temporary reduction in flowability on the first day. Fermentation improved the water-holding capacity, emulsification capacity, and stability, foaming stability, solubility, and swelling index of flours, while the oil-holding capacity and foaming capacity decreased. In addition, temperature had a pronounced impact on the solubility characteristics of the flours. The rheological analysis revealed that both mature and immature einkorn flours exhibited pseudoplastic and viscoelastic solid-like behavior throughout the fermentation process, with MEF generally showing higher viscosity and G ' values. Fermentation and maturation induced substantial modifications in structural features, protein interactions, and gelatinization behavior, resulting in significant variations in viscosity, elasticity, and flow behavior with increasing temperature and frequency. Fermentation and grain maturity affected flour colour, with immature einkorn flour exhibiting lower a* and higher b* values. This study highlights the effectiveness of fermentation in improving the functional and technological properties of einkorn wheat flour, supporting its application in cereal-based food products.
Keywords: Lactiplantibacillus plantarum; Wheat; Fermentation; Functional properties; Rheology; WHEAT-FLOUR; SOURDOUGH; DOUGH; IMPACT; STARCH; PH; Food Science & Technology